2023
DOI: 10.3390/jcm12144781
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Antibodies against the Acetylcholine Receptor in Patients with Myasthenia Gravis: A Comparison of Two Enzyme Immunoassays and a Fixed Cell-Based Assay

Abstract: The detection of serum anti-acetylcholine receptor (AChR) antibodies is currently an important tool for diagnosing myasthenia gravis (MG) since they are present in about 85% of MG patients. Many serological tests are now available. Nevertheless, results from these tests can be different in some patients. The aim of this study is to compare the sensitivity of a commercially available fixed cell-based assay (F-CBA) to that of enzyme-linked immunosorbent assay (ELISA) kits for anti-AChR detection in patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Studies assessing AChR-specific autoantibodies have compared ELISA, CBA, and RIPA in terms of specificity and sensitivity [ 13 , 14 , 15 ]. All these classical diagnostic assays can differentiate patients with MG from those with similar clinical presentations but different disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Studies assessing AChR-specific autoantibodies have compared ELISA, CBA, and RIPA in terms of specificity and sensitivity [ 13 , 14 , 15 ]. All these classical diagnostic assays can differentiate patients with MG from those with similar clinical presentations but different disorders.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the detection and measurement of serum anti-AChR antibodies performed by competitive ELISA (cELISA), indirect ELISA (iELISA), and an F-CBA, showed that cELISA has better performance analytics than iELISA and F-CBA. However, iELISA and F-CBA showed the greatest agreement [ 39 ].…”
Section: Serological Diagnosis: Different Methods Of Antibodies’ Dete...mentioning
confidence: 99%